China and Protectionism in Advanced Manufacturing: Why It is Prioritised and How It is Done - Widjanarko, Yeremia (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2025)
This study offered critical reinterpretation of China’s protectionist trade policies within its advanced manufacturing sector, focusing specifically on the development of the solar photovoltaic panels, electric vehicles, and lithium-ion batteries. By moving beyond normative justification for protectionism, the analysis employed the Infant Industry Argument as a solid theoretical lens to dissect the strategic rationale, institutional mechanisms, and specific policy instruments underpinning this state-driven initiative. The research employed a qualitative, case-study methodology, drawing on historical data from official government policy documents, industry reports, and numerous academic articles. The findings demonstrated that China’s success in practicing protectionist policies on its advanced manufacturing sectors stemmed not from passive or indefinite protection but from a dynamic and unique policy architecture. Its model strategically employed initial, timely-bounded subsidies and tariffs with the active promotion of market competition and clear performance benchmarks. This approach compelled firms to innovate and achieve economies of scale. Furthermore, the protection was deliberately made to be phased out, adapting industrial maturity through gradual liberalisation. Consequently, this strategy fostered globally competitive industrial champions, thereby avoiding the technological stagnation and market distortion in historical cases. This study concluded that China’s trajectory redefined the IIA as sophisticated governance strategy where protection was inherently conditional, competitive, and transitional, demonstrating its significant efficacy.